(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In the field of English as a Foreign Language (EFL), the diversity of learner types demands a flexible, student-centered approach. This paper examines the importance of EFL teachers’ ability to identify different learner types and adapt their teaching strategies accordingly. Based on cognitive, psychological, and educational research, it argues that effective differentiation enhances language acquisition, student engagement, and classroom management. The article outlines key learner typologies (visual, auditory, kinesthetic, analytical, global, etc.) and presents methodological approaches for diagnosing these types. It further discusses planning techniques for differentiated instruction and suggests strategies for professional development in this competence area.